Respuesta :
Step-by-step explanation:
Let's solve your equation step-by-step.
−5(x+7)=−5x+35
Step 1: Simplify both sides of the equation.
−5(x+7)=−5x+35
(−5)(x)+(−5)(7)=−5x+35(Distribute)
−5x+−35=−5x+35
−5x−35=−5x+35
Step 2: Add 5x to both sides.
−5x−35+5x=−5x+35+5x
−35=35
Step 3: Add 35 to both sides.
−35+35=35+35
0=70
Answer:
There are no solutions.
Answer:
x= no solution
Step-by-step explanation:
-5(x+7)=-5x+35
-5x-35=-5x+35
+5x +5x
-35= 35
+35 +35
0=70
x=no solution
When x doesn't equal anything, and 0 doesn't equal 0, there is no solution to make the equation true. When 0=0, x can equal any value.